Los «chamos» en cana - Pérez Guadalupe, José Luis (2024)
Following a chronic context of political crisis and violence (Antillano & Ávila, 2017; Antillano, 2023; Zubillaga & Llorens, 2023), Venezuela migration crisis of last years impacted on receptors countries such as Colombia and Perú (R4V, 2023). In particular, an exponential increase of foreign inmates in Peruvian prisons has triggered a renewed criminological discussion about migration and crime (Park et al., 1967; Brion, 1997). This article tackles an understudied aspect of this highly complex migration process: Venezuelans citizens facing pre-trial detention (74,5 %) or conviction sentences (25,5 %) in Peruvian prisons (INPE, 2024). Using a mixed methods approach we gathered statistics and conducted interviews of inmates and penitentiary agents to describe this new ‘coexistence’ in prisons. Furthermore, we discussed Venezuelan inmates’ adaptation vis á vis Peruvian prison culture and whether criminal groups could expand or transplant their activities (Varese, 2011; Garzón & Olson, 2013) to receptors country such as Panamá, Brazil, Colombia, Ecuador, Perú, Bolivia and Chile. Thus, we argue that cultural importation dynamics take place at Peruvian prisons and, moreover, conflict emerged between two prison cultures and convict codes (one of them involving an inmate self-government background and the other familiarized with dialogued ‘prison governance’ schemes); these two different visions of ‘what life in prison should be’ struggle to impose their own ways to recreate conviviality and survival.